The audit committees, internal audit and external audit quality effects on earnings management : an analysis of Malaysian government-linked companies - Ma, Wyei Leng; Noor Adwa Sulaiman; Azlina Abdul Jalil (Penerbit Universiti Kebangsaan Malaysia, 2022)
The role of audit governance mechanisms as part of the corporate governance architecture has been promoted to ensure the integrity of the financial reporting process. In order to get insights on their effectiveness, this study investigates the effects of the audit governance mechanism, specifically audit committee, internal audit function and external audit quality on earnings management in Malaysian government-linked companies. Using a cross-sectional variation of the modified Jones Model (1995) to estimate discretionary accruals, this study examined 38 GLCs from 2009–2018, which consisted of 340 firm-year pair observations. Panel data regression analysis was carried out using the generalised least square method to analyse the effect of audit governance mechanisms on earnings management. The findings suggest that lower likelihood of earnings management is associated with the internal audit function. Further analysis on the proxy of internal audit measures suggests that in-house internal audit function is negatively associated with earnings management. This research would provide insights for regulators and management to strengthen in-house internal audit function in order to mitigate earnings management in Malaysian government-linked companies